2018
DOI: 10.1002/hed.25107
|View full text |Cite
|
Sign up to set email alerts
|

Thirty‐day readmission in patients undergoing head and neck microvascular reconstruction

Abstract: More than 1 in 10 patients undergoing head and neck microvascular reconstruction has a 30-day unplanned readmission, most commonly related to wound complications. Further efforts are needed to determine optimal 30-day unplanned readmission reduction strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 24 publications
4
17
3
Order By: Relevance
“…Additional factors found to be independently associated with unplanned reoperation, such as prior wound infection, surgical site infection, and prolonged ventilation, are also consistent with previous literature as being related to free flap complications . Furthermore, another important finding from our study is the lack of significant association of reoperation with ASA classification.…”
Section: Discussionsupporting
confidence: 91%
“…Additional factors found to be independently associated with unplanned reoperation, such as prior wound infection, surgical site infection, and prolonged ventilation, are also consistent with previous literature as being related to free flap complications . Furthermore, another important finding from our study is the lack of significant association of reoperation with ASA classification.…”
Section: Discussionsupporting
confidence: 91%
“…These findings in the overall MVFTT population are similar to those discovered in our immunosuppressed cohort where 21% experienced donor or recipient site wound dehiscence, 13% had a hematoma, and 4% developed a postoperative wound infection, suggesting that pharmacologic immunosuppression alone is not associated with increased postoperative wound issues. Similarly, our average length of stay (8 days) compares favorably to that reported by Cannady et al in their analysis of the NSQIP database (11.6 days) with a comparable 30‐day readmission rate (11%) to that reported previously in the literature (5.1%–16.1%) despite the medical complexity of the patients of our cohort, suggesting that MVFTT can be performed safely in this population 21,28 …”
Section: Discussionsupporting
confidence: 88%
“…Similarly, our average length of stay (8 days) compares favorably to that reported by Cannady et al in their analysis of the NSQIP database (11.6 days) with a comparable 30-day readmission rate (11%) to that reported previously in the literature (5.1%-16.1%) despite the medical complexity of the patients of our cohort, suggesting that MVFTT can be performed safely in this population. 21,28 Regarding pharmacologically immunosuppressed patients, several studies investigating utilization of MVFTT in patients with solid organ transplantation have been published with overall complication rates as high as 54% and flap failure rates of 0%-4.5% reported. 5,6,29 Sbitany et al reported a series of 24 solid organ transplant recipients who underwent MVFTT (including 10 in the head and neck) and found prednisone to be associated with overall complication rate (26% vs. 80%, p = 0.03).…”
Section: Discussionmentioning
confidence: 99%
“…Wound dehiscence describes separation of the approximated margins of a surgical incision 30 . There is an association between wound dehiscence and smoking, prior radiotherapy (particularly in excess of narrow‐field techniques), and poor preoperative nutritional status 31–33 . In the context of head and neck reconstruction, neck incisional dehiscence may present secondary to fistula formation, salivary leak, and/or infection.…”
Section: Resultsmentioning
confidence: 99%
“…30 There is an association between wound dehiscence and smoking, prior radiotherapy (particularly in excess of narrow-field techniques), and poor preoperative nutritional status. [31][32][33] In the context of head and neck reconstruction, neck incisional dehiscence may present secondary to fistula formation, salivary leak, and/or infection. It is important to distinguish that wound dehiscence is not synonymous with fistula.…”
Section: Consensus Termsmentioning
confidence: 99%